Learning of Reaction Rates Materials with Curricular Structuring Nested Assisted by Schoology Application to Improve Students Critical Thinking Skills and Learning Outcome (UNESA Journal of Chemical Education, 2019)
This study aimed to evaluate the learning process of reaction rate materials with curricular structuring nested which the implementation of this learning that assisted by schoology applications. Evaluation of this learning was based on two variables, which were the improvement of students critical thinking skills and learning outcome in the reaction rate materials. The learning is designed and implemented using a scientific inquiry model. This study was pre-experimental and followed one group pretest-posttest design. The subjects of this study were 36 students of 10th grade at State of Senior High School 1 Manyar Gresik (SMAN 1 Manyar Gresik). The results showed that the learning of reaction rate materials with curricular structuring nested assisted by schoology applications was can be carried out with quality in the good to very good category to the lesson plan. Students critical thinking skills and learning outcome have increased significantly, but there were students who get posttest scores that not reached passing grade. This learning of reaction rate materials with curricular structuring nested assisted by schoology applications can be well received by students based on the responses of students with gave positive response was 94,44%.